Navigating Urban Environmental Hazards: Policies and Pathways to Health Equity in Pakistan within the Framework of Sustainable Development Goals - Aleesha Abbas; Taha Hussain; Hamid Hussain; Shumaila Arif; Saman Batool (Journal of Management Practices, Humanities and Social Sciences, 2024)
A Potential Time Bomb, as discussed in our study, has serious urban environmental risks in Pakistan, particularly in achieving the Sustainable Development Goals (SDGs) (UN). Rapid urbanization has led to higher pollution, insufficient waste management, and stressed infrastructure, disproportionately hurting communities with limited resources and impeding progress toward health equity. Our research has significant limitations that must be understood. Our analysis studies explore how inequality affects environmental threats in Pakistani urban areas, particularly Lahore. Our team discovered facts about pollution by speaking with residents. Our findings show that effective environmental protection needs both city planning and community efforts, plus national government rules.